PERANCANGAN SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA UMKM MADU ASLI ZHAFIRA DENGAN MENGGUNAKAN DATABASE MYSQL - Edy Siswanto; Zhafira Fikri Nada; Moh Muthohir; Teguh Setiadi (Informatika: Jurnal Teknik Informatika dan Multimedia, 2025)
The purpose of this study is to overcome problems occurring at UMKM Madu Asli Zhafira by creating a Web-Based Sales Information System using PHP & HTML programming languages and a MySQL database. The author used the RAD (Rapid Application Development) method for designing the information system, as this method uses an object-oriented approach to development. Using this method also speeds up the process and minimizes costs. The newly built system produces structured outputs that include product data, price data, product stock, product category data, account data, user data, and sales report data. In addition, this system offers important reports that enable UMKM Madu Asli Zhafira to collect information efficiently and accurately.